Nickel‐Catalyzed α‐Allylation of Aldehydes and Tandem Aldol Condensation/Allylation Reaction with Allylic Alcohols. (29th May 2017) - Bernhard, Yann; Thomson, Brodie; Ferey, Vincent; Sauthier, Mathieu
Abstract: An additive‐free nickel‐catalyzed α‐allylation of aldehydes with allyl alcohol is reported. The reaction is promoted by 1 mol % of in situ formed nickel complex in methanol, and water is the sole by‐product of the reaction. The experimental conditions allow the conversion of various α‐branched aldehydes and α, β‐unsaturated aldehydes as nucleophiles. The same catalyst and reaction conditions enabled a tandem aldol condensation of aldehyde/α‐allylation reaction.